PARTICIPATORY BUDGETING AS A TOOL FOR ENHANCING GOVERNMENT TRANSPARENCY AND ACCOUNTABILITY CASE STUDIES FROM EMERGING ECONOMIES - Purwanti, Ari; Fresiliasari, Oktavie; Alfaruq, Zakiyuddin Abdul Malik; Sudjono, Sudjono; Sukomardojo, Tekat (CosmoGov: Jurnal Ilmu Pemerintahan, 2024)
Participatory budgeting is increasingly becoming a major focus in improving government transparency and accountability, particularly in developing countries. In contexts often impacted by social, economic, and political challenges, this process offers an opportunity to improve public governance. However, the implementation of participatory budgeting faces several obstacles such as bureaucratic resistance and resource constraints. This study explores how participatory budgeting can improve government transparency and accountability in developing countries. The study used a qualitative approach, collecting data from a variety of relevant sources, and analyzing the data to identify key findings. The results of the study show that despite significant challenges, participatory budgeting offers a significant opportunity to improve public governance by involving citizens in the budget decision-making process. Citizen participation can identify often overlooked local needs and strengthen the relationship between government and citizens. However, the success of participatory budgeting implementation depends heavily on political commitment and bureaucratic reforms that support openness and public participation. With adequate support, participatory budgeting can contribute to more inclusive and sustainable development.gb777